Developing young talent to olympic champions in athletics. Understanding realistic progressions - Cardinale, M. (ASPETAR Sports Medicine Journal, 2019)
Athletics is quite possibly the most ancient sport in the Olympic programme. It is a collection of sporting events that involve running, jumping, throwing and walking and it has been documented since the ancient Olympics. Athletics is in fact one of the only five sports that have been contested at every summer Olympic Games since 1896 with a current programme of 24 events contested in the Olympic programme. National and continental and World events are also contested at various age groups (youth and junior categories) as well as youth Olympic Games since their inception in 2010.